El sistema de continuidad como proceso unificador - Prósper Ribes, Josep (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2007)
The continuity system is a procedure of construction of audio-visual stories with the narrative causality how foundation and a set of elaboration norms, specially in the assembly, whose purpose is to show al watching a logical argumental development that it is developed in a coherent diegetic space-time. The continuity, is put under an ideological model of representation that conditions the perception.